2008
DOI: 10.1111/j.1365-2133.2008.08452.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective randomly selected cohort study of D-penicillamine treatment in rapidly progressive diffuse cutaneous systemic sclerosis of recent onset

Abstract: In a population of patients with diffuse cutaneous systemic sclerosis, with progressive disease of recent onset, D-penicillamine treatment at a median dose of 750 mg per day caused a statistically significant reduction in skin involvement and improvement of renal, cardiac and pulmonary involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Furthermore, these results are also superior to our previously published data on D-penicillamine in a similar population (22). These results are also superior to the spontaneous reduction in mRSS observed in the placebo control group (-4.6) and in the relaxin-treated group (-4.4) in a recently published study describing the results of a 24 week randomized control trial of human recombinant relaxin in a population of SSc patients similar to the one we studied here (26) and to the -3 point reduction at 15 months in either placebo or treated group in patients with early phase SSc entering the bovine type I collagen randomized control trial (27).…”
Section: Discussionsupporting
confidence: 35%
See 2 more Smart Citations
“…Furthermore, these results are also superior to our previously published data on D-penicillamine in a similar population (22). These results are also superior to the spontaneous reduction in mRSS observed in the placebo control group (-4.6) and in the relaxin-treated group (-4.4) in a recently published study describing the results of a 24 week randomized control trial of human recombinant relaxin in a population of SSc patients similar to the one we studied here (26) and to the -3 point reduction at 15 months in either placebo or treated group in patients with early phase SSc entering the bovine type I collagen randomized control trial (27).…”
Section: Discussionsupporting
confidence: 35%
“…The effects of MMF on the extent and severity of skin involvement employing the modified Rodnan Skin Score (mRSS) and an estimate of extent of affected body surface area (BSA) were 5 assessed as described previously (22). The effects of MMF on SSc severity employing some of the categories of Medsger's severity scale (23) were also examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with data from Pittsburgh in 1985 (60) where the use of D-penicillamine for SSc ILD was found to improve DLCO significantly, with no progression of dyspnoea symptoms. This was confirmed in 1987 in a smaller study by de Clerck et al (61) , and more recently by Derk et al in 2001 (62) .…”
Section: Interstitial Lung Disease Treatment In Systemic Sclerosismentioning
confidence: 67%
“…A large randomized double-blind trial involving patients with early diffuse cutaneous scleroderma demonstrated that a low dose of 125 mg every other day may be as effective as higher doses of 750-1000 mg/day [40]. In a recent study, a dose of 750 mg/day in patients with rapidly progressive diffuse systemic sclerosis caused a significant reduction in skin thickening and improvement of renal, cardiac and pulmonary involvement [41]. Monitoring is required for side effects, such as autoimmune pheno menon (pemphigus and myasthenia gravis), hematological abnormality and proteinuria.…”
Section: Targeting the Immune Systemmentioning
confidence: 99%